Cinema e Inclusão: Uma alternativa metodológica para debater a inclusão com o uso do Cinema nos Anos Iniciais do Ensino Fundamental - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
This dissertation is part of the research line Practices and Training Processes of Educators for Inclusive Education of the Postgraduate Program in Inclusive Education of the State University of Ponta Grossa/PR. The object of study is Cinema in the classroom from the perspective of the inclusive teaching process, aiming at the training of teachers of the Initial Years of Elementary Education. We set it as a research problem: “How can the use of Cinema as an artistic language and educational tool promote a more effective reflection on inclusion in the school environment?” Thus, we search for possible answers. The general objective of the research is to contribute with a methodological possibility in the continuous training of teachers for the applicability of Cinema as a means of reflecting and raising awareness about inclusion with Basic Education students of the initial years of Elementary Education in the city of Ponta Grossa. Based on the general objective, some specific objectives were listed: a) implement a teaching project based on the use of Cinema as a tool to promote reflection and awareness about inclusion in Elementary Education; b) Investigate the perceptions of the researched subjects in relation to the use of Cinema as a means of promoting inclusion; c) Verify the effects of the use of Cinema as a means of promoting inclusion on the perception and engagement of elementary school students. The theoretical framework is mainly composed of authors such as: Libâneo (2012); Carvalho (2004); Sassaki (2009); Bordwell and Thompson (2009) Benjamin (1937); Martin (2002); Fresquet (2105); Duarte (2002) among others. This is a qualitative research of a descriptive nature, outlined in participatory action research. Based on this methodology, the analysis of the materials whose data were integrated based on the drawings made by the students, the result of the film analysis from the stage considered symptomatic of the film analysis methodology of Suarez (2018), is carried out. The results show that the use of cinema from the perspective of inclusion is a significant ally in the educational process, evidencing its potential to enrich pedagogical practice. Furthermore, cinema proves to be a valuable resource for the ongoing training of early-year teachers, providing new opportunities for professional development and improvement of inclusive practices in the classroom.
Keywords: Formação continuada de Professores; Educação Inclusiva; Cinema; Artes Visuais; Continuing Teacher Training; Inclusive Education; Cinema; Visual Arts; CNPQ::CIENCIAS HUMANAS::EDUCAÇÃO